Tree girdling and host tree volatiles provides a useful trap for bronze birch borer Agrilus anxius Gory (Coleoptera: Buprestidae). (31st March 2019) - Silk, Peter J; Ryall, Krista L; Grant, Gary; Roscoe, Lucas E; Mayo, Peter; Williams, Martin; LeClair, Gaetan; Kimoto, Troy; Williams, David; Rutledge, Claire
Abstract: The bronze birch borer, Agrilus anxius, is a North American buprestid pest of stressed or weakened birch trees ( Betula spp.) and is considered a major threat to European birch species as a potentially adventive insect. Laboratory bioassays and field trapping experiments were conducted to elucidate potential visual and chemical cues used in host location in this species. Birch bark and foliar volatiles ( Betula papyrifera Marsh) and a pheromone attractive to the congener, A. planipennis, (3 Z )-dodecen-12-olide ((3 Z )-lactone), were tested along with a girdled tree treatment, with purple sticky prism traps. Only the girdled tree treatment with purple traps elicited significant attraction by adult A. anxius . Various colours of sticky traps were tested with host volatiles attractive to A. planipennis ; results showed that unbaited green sticky traps were more attractive than other colours tested; none of the host volatiles tested increased trap capture with any traps. Examination of foliage and bark of B. papyrifera by GC/EAD, and GC/MS techniques has identified several EAD-active compounds with (3 Z )-hexenol and (5 S, 7 S )-conophthorin as the most EAD-active molecules. Neither compound, however, alone or combined, elicited significant trap capture on green sticky prism traps; these compounds may find importance as synergists once the pheromone for A. anxius is identified.